The Effect of the Application of Doctor Rubini's Biography as a Resource for Learning History on the Critical Thinking Ability of Class XI of SMA Negeri 1 Tebas - Rosita, Mita Dea; Putri, Astrini Eka; Prabowo, Mohammad Rikaz (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This study was conducted to determine the effect of the policy of Dr. Rubini's biography as a source of learning history on the critical thinking skills of class XI students of SMA Negeri 1 Tebas. The method used was an experiment with a Pre-Experimental Design design and data analysis using the swimmer test and the dependent sample t-test. The data sources in this study were history teachers, class XI students, and learning media. The results showed that the average pretest score of 54.83 was in the moderate category, while the average posttest score increased to 65.32 in the good category. The low initial ability of students was due to the low exploration of local values in history learning. After the application of Dr. Rubini's biography, there was a significant increase in critical thinking skills. The results of the t-test showed a significance value of 0.001 <0.05, which means that there is a significant influence of the application of the biography on students' critical thinking skills.